(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study investigates the impact of knowledge conversion on innovation and organizational performance through a multi-layered moderated mediation framework. Drawing on the SECI model (socialization, externalization, combination, and internalization), the research examines how different modes of knowledge conversion influence both incremental and radical innovation outcomes, which subsequently shape overall organizational performance. The study also explores how organizational culture and digital knowledge infrastructure moderate the relationships within the framework. Data were collected from 412 IT professionals working in knowledge-intensive and innovation-driven environments across multiple organizations. Using structural equation modelling (SEM), the study empirically validates the proposed framework and reveals that knowledge conversion significantly enhances innovation capability, and innovation acts as a strong mediator between knowledge conversion processes and performance outcomes. Furthermore, supportive organizational culture and robust digital infrastructure significantly strengthen the indirect effects, confirming a multi-layered moderated mediation effect. The findings highlight the strategic importance of investing in knowledge conversion mechanisms to foster innovation and drive sustainable organizational performance. This study contributes to the knowledge management and innovation literature by offering a deeper understanding of how knowledge processes interact with contextual factors to influence performance in IT-driven environments. It also provides practical implications for managers seeking to enhance innovation capability through effective knowledge management practices.